Evaporation rate effect on starting point of shrinkage stress development during drying process in solvent cast polymer film. Issue 1 (22nd June 2012) - Katsumata, Reika; Ata, Seisuke; Kuboyama, Keiichi; Ougizawa, Toshiaki
Abstract To reveal the effect of drying conditions on shrinkage stress existing between a film and a substrate, a polystyrene/toluene solution was coated on a glass substrate, and the volume fraction of toluene at the time when the stress starts to grow (ϕS) was measured at various drying temperatures and evaporation rates. ϕS decreased with increase of drying temperature at a constant evaporation rate, while ϕS increased with increase of evaporation rate at a constant drying temperature. From these results, it was suggested that the dominant factors affecting the starting point of stress were both the chain mobility and the measurement time‐scale. Considering the two factors, the tendency of ϕS with the drying conditions is quite similar to that of the solvent content at glass transition point, and this fact indicates a strong correlation between the starting point of stress and the glass transition of coated solution. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013